Organisational learning in SMEs: a process improvement perspective. Issue 7 (3rd July 2017) - Matthews, Rupert Lawrence; MacCarthy, Bart L.; Braziotis, Christos
Abstract : Purpose: The purpose of this paper is to investigate how organisational learning (OL) can occur through process improvement (PI) activities, leading to sustained improvements over time in the context of small- and medium-sized enterprises (SMEs). Design/methodology/approach: The authors study PI practices in six engineering-oriented SMEs via interview-based case studies. The authors draw from a range of literature and use an OL conceptual framework informed by Crossan et al. 's (1999) 4I framework as an analytical lens. Findings: The OL perspective provides new insights to conceptualise the nature of PI as a multi-level practice in SMEs. Effective PI practices within SMEs are shown to be consistent with OL concepts, enabling firms to translate individually identified improvement opportunities into organisational-level changes that result in sustained benefits. A new conceptual model is presented that explains how SMEs can learn through improvement activities. The key role of management support, both operational and strategic, is highlighted. It is necessary for management to provide sufficient PI opportunities to enable and sustain beneficial learning. Research limitations/implications: The study is based on a sample of engineering-oriented SMEs located in the UK. Further case-based, longitudinal, and survey-based research studies with firms of different types will enhance the generalisability of the findings, allowing the confirmation and extension of the new conceptual model. Practical implications: The findings provide a theoretically underpinned framework for achieving OL in engineering-oriented SMEs through PI activities. The new model highlights the key mechanisms that enable learning from improvement activities. The findings highlight the key role played by management in introducing additional learning opportunities in the form of new business that requires exploratory learning. Without this, the reduction in improvement opportunities reduces the benefits that can be realised from PI. Originality/value: OL provides a multi-level perspective to understanding how smaller firms are able to undergo systematic improvements and the support required to continually improve.